ANALISIS MOTIVASI BELAJAR MATEMATIKA SISWA SMA BINGKAI CENDEKIA CILILIN BERBANTUAN APLIKASI GEOGEBRA PADA MATERI TRANSFORMASI GEOMETRI (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze student learning motivation through the application of Geogebra on Geometry Transformation course. The research method used was a descriptive research. The population in this study were all high school students at Kabupaten Bandung Barat with the sample used were 25 XI grade students at SMA Bingkai Cendikia Cililin. Data collection techniques using a questionnaire scale of student learning motivation towards learning mathematics assisted by Geogebra application that contains 20 statements each of 10 positive and negative statements. The results of the analysis in this study indicate that students are motivated by the use of the Geogebra application, this can be seen from the 75% student interest in the indicators of interesting activities in learning, because learning is packaged attractively through the presentation on the Geogebra application. So that almost all students are aroused to have ambition and desire to succeed in learning with a percentage of 82%. It also affects the appreciation of students in learning that has a positive impact with a percentage of 72.5%.